Usability of Augmented Reality (AR) Application in ‘Fertigation System’ among Form 1 Students at Sekolah Menengah Kebangsaan Behrang 2020, Perak, Malaysia - Asilah Abdul Mutalib; Nurfatin Masliza Mohamed Imran; Zalina Ismail; Zahidah Ab Latif; Shaibatul ’ Islamiah Che Man; Noor Hidayah Azmi (Journal of Vocational Education Studies, 2022)
The purpose of teaching aid is important to attract students to always be active in the classroom. It is important to focus on educational activities among students such as the usage of teaching aid during the teaching and learning process. Therefore, the objective of this study is to identify the usability of augmented reality (AR) application 'Fertigation System' among form 1 students of SMK Behrang 2020 who took Design and Technology subject. The application was developed using the ADDIE model which has five phases including analysis, design, development, implementation, and evaluation. The design of the studies used was quantitative method (survey method). The instrument of study used was a questionnaire. In the first phase (Analysis), a questionnaire that was endorsed by experts was distributed to 35 respondents to identify the needs of the AR application development. In this phase, there were 72% of respondents agreed the needs of the AR application development. For the next phases, an AR 'Fertigation System' has been designed and developed. A questionnaire was distributed together with the AR application that has been developed and verified by three experts from different fields (language, education, content). After that, a pilot study was conducted among 50 students of form 1 who took Design and Technology subject at SMK Behrang 2020 as respondents for improvement purposes (Implementation phase). For the final phase (Evaluation), a questionnaire and application of AR 'Fertigation System' which has been verified and improved was distributed to 76 respondents comprising form 1 students who took Design and Technology subject at SMK Behrang 2020. The results of this study showed that 62.72% of the respondents strongly agreed with the usability of the AR application 'Fertigation System'. All data obtained was analyzed using the Statistical Package for Social Science (SPSS) to obtain the average value, percentage, frequency and standard deviation. In conclusion, the results of this study show that the AR application of the 'Fertigation System' that has been developed can be used among form 1 students who took Design and Technology subject at SMK Behrang 2020, Perak.